A new prognostic model for primary sclerosing cholangitis - Acar, Şencan; Akyıldız, Murat (Turkish Journal of Gastroenterology, 2019)
Cite this article as: Acar Ş, Akyıldız M. A new prognostic model for primary sclerosing cholangitis. Turk J Gastroenterol 2019; 30(11): 1004-6.